Laminar profile of spontaneous and evoked theta: Rhythmic modulation of cortical processing during word integration. (September 2015) - Halgren, Eric; Kaestner, Erik; Marinkovic, Ksenija; Cash, Sydney S.; Wang, Chunmao; Schomer, Donald L.; Madsen, Joseph R.; Ulbert, Istvan
Abstract: Theta may play a central role during language understanding and other extended cognitive processing, providing an envelope for widespread integration of participating cortical areas. We used linear microelectrode arrays in epileptics to define the circuits generating theta in inferotemporal, perirhinal, entorhinal, prefrontal and anterior cingulate cortices. In all locations, theta was generated by excitatory current sinks in middle layers which receive predominantly feedforward inputs, alternating with sinks in superficial layers which receive mainly feedback/associative inputs. Baseline and event-related theta were generated by indistinguishable laminar profiles of transmembrane currents and unit-firing. Word presentation could reset theta phase, permitting theta to contribute to late event-related potentials, even when theta power decreases relative to baseline. Limited recordings during sentence reading are consistent with rhythmic theta activity entrained by a given word modulating the neural background for the following word. These findings show that theta occurs spontaneously, and can be momentarily suppressed, reset and synchronized by words. Theta represents an alternation between feedforward/divergent and associative/convergent processing modes that may temporally organize sustained processing and optimize the timing of memory formation. We suggest that words are initially encoded via a ventral feedforward stream which is lexicosemantic in the anteroventral temporal lobe; its arrival may trigger a widespread theta rhythm which integrates the word within a larger context. Graphical abstract: Highlights: We used microelectrode arrays to define the circuits generating theta in humans. Theta was generated by excitation alternating between input and association layers. Baseline and word-evoked theta have the same generators. Cognitive event-related potentials may represent reset theta. Theta may help support extended and widespread cognitive processing.